‘British Capital, Industry and Perseverance’ versus Dutch ‘Old School’?: The Dutch Atlantic and the Takeover of Berbice, Demerara and Essequibo, 1750-1815 - Oostindie, Gert (BMGN - Low Countries Historical Review, 2012)
Recent historiography has reconsidered the idea that the Dutch role in the early modern Atlantic was of little significance, particularly in comparison to the accomplishments of the Dutch East India Company (voc) in Asia. Revisionist studies have emphasised that in spite of the limited and fragmented nature of the Dutch Atlantic ‘empire’, the Atlantic contribution to the Dutch economy was significant and possibly even greater than the voc’s share. Moreover, this scholarship stresses the vital role of Dutch Atlantic colonies (Curaçao and St Eustatius), (partly Jewish) networks and individuals in connecting the various subempires of the Atlantic. While Oostindie subscribes to many of these conclusions, he argues against excessive revisionism. His analysis of the development of the lesser Dutch Guianas, adjacent to Suriname, is used as a counter-weight to this revisionist impulse. He demonstrates that the spectacular economic and demographic development of these colonies was due mainly to British and (British) American involvement culminating in the eventual British takeover of ‘Guiana’.